Autophagy and Premature Graying of Hair: The Role of LC3 as a Biomarker in a Case-Control Study - Wafaa Mohamed Abd-Elmaged; Khaleda S Amr; Hoda A Ahmed; Dina Ali; Amr Abdelhamed (Dermatology Practical & Conceptual)
Introduction: Premature graying of hair (PGH) is a common disorder with a multifactorial etiology. Autophagy, which is self-cellular digestion, has been linked to melanin pigment formation; however, the role of autophagy in PGH has not been investigated well.